Interconnection of Konwledge Science, Islamic Religion and Philosophy of Science - Luhuringbudi, Teguh; Utami, Dewi Nita; Purnomo, Halim (Khatulistiwa, 2020)
This paper seeks to highlight the similarities and differences of science, Islam, and the philosophy of science. The discussion of this paper begins with the assignment of definitions of these three topics. The next discussion is the concept of the three such as the three components of science and the four requirements or rules of science; teachings and objectives of Islam; and the two tasks, objects, and benefits of the philosophy of science. The relation between science and philosophy of science is evidenced from the structure of objectivity, the subjectivity of scientists, and the efforts of control or judgment. The relationship between religion and philosophy of science can be seen from the dominance of morality in the ideal imagination as a standard of product, attitude, and activity. Another proof of the relationship between Islam and the philosophy of science is the variant of Islamic epistemology in the form of bayānī, burhānī, and 'irfānī. The relationship between science and religion of Islam is reflected in the appreciation of al-Qur'ān and al-Ḥadīth which is responded by the presence of religious educational institutions primordially.